“Treat-and-Extend” Regimen for Exudative Age-Related Macular Degeneration: A Two-Year Retrospective Follow-up Study - Riecke, Julian; Valmaggia, Christophe (Klinische Monatsblätter für Augenheilkunde, 2022)
Background After the introduction of a “treat-and-extend” regimen (T&E) with aflibercept for exudative age-related macular degeneration, naive eyes were compared with eyes pretreated with a “pro re nata” scheme (PRN).Patients and Methods The Ethics Committee of Eastern Switzerland approved the retrospective single-centre study (EKOS20/084, project ID: 2020-01193). The study included 342 eyes of 303 patients newly treated with or switched to T&E between January 2018 and March 2018 at the Eye Clinic of the Cantonal Hospital St. Gallen. The gender distribution of the treated eyes was 63.5% (n = 217) female and 36.5% (n = 125) male. The mean age was 81.6 years (SD = 8.6 years). The collective was divided into three groups: 1) naive, untreated eyes (n = 92), 2) eyes with ≤ 6 previous treatments with PRN (n = 37), 3) eyes with > 6 previous treatments with PRN (n = 213). The following parameters were analysed up to December 2019: the evolution of visual acuity, the number of intravitreal injections, the number of recurrences, the duration of the follow-up, the dropout rate, and the duration of the last treatment interval.Results During the observation period, group 1 showed a statistically significant improvement in visual acuity of + 1.5 ETDRS, while groups 2 and 3 showed a decrease in visual acuity of − 2.9 and − 3.7 ETDRS, respectively. Group 1 had better development of visual acuity than groups 2 and 3 (p = 0.005), while groups 2 and 3 were not significantly different (p = 0.92). The other parameters examined in the three groups did not differ significantly between groups.Conclusions Treatment with aflibercept in T&E shows significantly better visual acuity in naive eyes than in eyes pretreated with PRN.
Keywords: age-related macular degeneration; “treat-and-extend” regimen; anti-vascular endothelial growth factor; real-life data